Vendor Rating Using Analytical Hierarchical Process - Insights from Indian Engineering Construction Industry (International Journal of Scientific Research and Management (IJSRM), 2018)
Vendor Evaluation and Selection is one of the most critical activities of purchasing management in supply chain. It is a complex problem involving qualitative and quantitative multi-criteria. A trade-off between these tangible and intangible factors is essential in selecting the best supplier. This paper aims to develop a vendor rating system for Engineering Construction Industry where there is a huge involvement in the purchases of Pipes (like Ductile Iron, Mild Steel, HDPE, RCC, PVC), Pumps, Electrical items (like Panels, PLC, Motors, Generators) and Mechanical items for Water & Effluent Treatment Projects. The conventional method is less accurate in ranking the vendors as a result of greater amount of subjectivity.This paper focuses on developing a Vendor Rating System using AHP methodology to choose the best suppliers in such a way to reduce the time taken for the selection process.